Two Forms of Humanism: André Malraux and Romain Gary - Hangouët, Jean-François (Literatūra, 2022)
This article purposes to shed a mutual light on André Malraux’s humanism on the one hand, and on Romain Gary’s on the other hand. Our approach consists in juxtaposing their views on some of those faculties which, in the interaction of the living with the world, seem specific to mankind: the collective faculties of fraternity, culture, and science, the metaphysical abilities to ponder death, cosmos, and evolution. Malraux views fraternity as a “virile” instinct that best manifests itself during warfare, and Gary makes it feminine and akin to “universal love”. While Malraux, most classically, opposes culture to nature, Gary, in an original perspective, sees culture as a new “nurturing environment”. Malraux does not believe in science as a metaphysical incentive, but Gary finds its results stimulating. Malraux tends to think (somewhat paradoxically) about “man’s fate” (at an ontological level) through the (sole) metamorphosis of the works of art as produced in the historic period up to his days. In a broader perspective, Gary considers the biological evolution of mankind over geological ages, methodically starting with the late Devonian when lungless creatures crept up from sea to land, and hopefully envisioning the end result of the twenty thousand years to come. Malraux’s cosmos is a rival to mankind, while Gary sees humanity at home in the universe. Malraux is obsessed with individual death to the point of concluding that any meaning assigned to human lives is nothing but aleatory. Gary has faith instead in the “joy of being” during one’s lifetime, and in the continuous progress of humanity as a species. In such mutual lights, it appears that Malraux’s humanism, not unlike the most melancholic currents of romanticism, is tragic indeed, as many critics have already noted: desolate (man is alone) and devastated (devoid of meaning). As to Gary’s humanism, it comes out as relatable to Julian Huxley’s evolutionary humanism, and no longer as desperate as a certain, inexplicably vivacious, academic tradition still claims it to be. By contrast with Malraux’s, it appears to be actually full of consideration for a wide variety of human interests, yearnings and dreams. It is tactfully expressed in a way that stimulates hope. And its fictionalized form is masterly, not only in terms of novel-writing (Gary’s books being so unlike thesis novels) but also in terms of analytical thinking and philosophical foundation.